Arab Gulf cities: competing identities of cosmopolitanism vs. localism - Jarach, K. (2013)
Arab cities in the Gulf have changed rapidly and massively within a very short period. Historically, their economies were based on trade, and they have always been cosmopolitan, maintaining a delicate balance between inclusion and exclusion of various ethnic and religious groups. In the post-oil world, many factors combined to tilt the balance toward exclusion. We examine the traditional balance, and key factors that have upset that balance. These include the shift in the economic foundation of the city, vastly increased scale of migration, shifting relations between the political elite and the major merchant houses, and changing interaction between the city and tribes people of the local hinterland